A Hybrid UV-Vis Spectroelectrochemical Approach for Measuring Folic Acid using a Novel Ni-CNF/ITO Electrode. (1st October 2022) - Ali, Haider; Verma, Nishith
Highlights: A folic acid sensor developed based on UV-Vis spectroelectrochemistry. Electrocatalytic Ni-tipped CNFs used for non-selective oxidation of folic acid. UV-Vis absorbance-based measurements performed over 1 – 100 µg/ml range. Successfully tested in the interfering species containing pharmaceutical tablets. The fabricated sensor exhibited a linear response with the LOD of 0.14 µg/ml. Abstract: A folic acid (FA) sensor based on UV-Vis spectroelectrochemical technique was developed for the first time using Ni-tipped carbon nanofibers (Ni-CNFs) anchored over an optically transparent indium tin oxide (ITO) electrode. In a novel approach, the biomolecules including FA were oxidized by the Ni-CNF electrocatalyst, and the oxidized folate species were spectrophotometrically detected without requiring any specific recognition element. The electrocatalytic Ni-CNFs, synthesized using chemical vapor deposition technique, increased the electrochemical surface area, thus improving the sensitivity and reducing the charge transfer resistance required for the electro-oxidation of FA. The concentration levels of the oxidized folate species were measured at the characteristic wavelength of 400 nm using the coupled UV-Vis spectroscopy, The sensor performed linearly in the FA range 1 – 100 µg/ml, in the presence of interfering molecules, namely ascorbic acid, uric acid, vitamin – B12, and glucose. The limit of detection was determined as 0.14 µg/ml. The sensor was also successfully tested in commercial multivitamin tablets. In the future study, a sensor based on the hybrid UV-Vis spectroelectrochemical approach can be developed for the measurements of biomolecules such as dopamine, epinephrines, and vitamin B-12, where quantitative measurements using independent spectrophotometric and electrochemical technique are challenging because of convoluted peaks in either cyclic voltammogram or UV-Vis spectra. Graphical Abstract: Image, graphical abstract